Ant Colony Optimisation with Breslauer Nearest-Neighbour Thermodynamic Parameter for DNA Sequence Design in DNA Computing - Zuwairie, Ibrahim; Mohd Falfazli, Mat Jusof; Mohd Zaidi, Mohd Tumari (2014)
The process of designing a set of good DNA sequences is an essential problem and one of the most practical and important research topics in DNA-based computing. In this field of research, a DNA sequence design problem is defined as a multi-objective problem, and it is evaluated using four objective functions, which are h-measure, similarity, continuity, and hairpin. In addition, two constraints, GC content and melting temperature, are used to maintain uniform chemical characteristics of the sequences. In the authors' previous research, ant colony system (ACS) was proposed to solve the DNA sequence design problem and the Watson-Crick base pair ΔGo37 was used as the distance between nodes in the computational model of DNA sequence design. In the current study, the use of other parameters, namely, Breslauer nearest-neighbour thermodynamic parameters are investigated and the result is compared with the previous work.